RANCANG BANGUN OMNI WHEELS ROBOT DENGAN RODA PENGGERAK INDEPENDENT - Syam, Rafiuddin; Irham, Irham; Erlangga, Widhi (Jurnal MEKANIKAL, 2012)
Omniwheels robot is a kind of mobile robot that can be moved to any direction, different cases than non-holonomic mobile robot. The advantage of omniwheels is shape of the wheel. Control method of this research is kinematic control. The derivation of such method is matrices velocities of omniwheels robot.Than, the control system was implemented to tracking trajectory problem. Still in the control system, it was choosing closed loop control for auto navigation problem. Finally, the robot also was used ultrasonic sensors for obstacle avoidance problem.